Evaluation of Pregnant and Postpartum Women's Knowledge about Toxoplasmosis in Rio Grande - RS, Brazil - Lis Maurente Lehmann; Paula Costa Santos; Carlos James Scaini (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2016)
Abstract Introduction Toxoplasmosis a parasitic zoonosis of global distribution, responsible for disorders during gestation can cause fetal death or congenital anomalies. Objective To evaluate the knowledge of toxoplasmosis among pregnant and postpartum women treated at the University Hospital of the city of Rio Grande, Rio Grande do Sul, Brazil. Methods This was a cross-sectional study of 100 pregnant and postpartum women at the University Hospital. Participants answered a self-administered questionnaire and gave consent for data relating to serological examinations to be abstracted from their medical records. Results The proportion of women who received information about toxoplasmosis was higher among those who received care in the private health care system (52.9%) than among those cared for in the public health care system (25.0%). Only 55.7% of women reported having some knowledge about toxoplasmosis. Of these, 53.7% received information during the prenatal period. However, most participants were unable to answer questions about preventive measures and modes of infection. Of the 100 patients in the study, only 46 underwent serologic testing for toxoplasmosis, 65.2% of whom tested negative (IgG). Conclusion Findings from this study are relevant to the training of health professionals regarding toxoplasmosis education and prevention. Improved education for health care providers and patients can lead to earlier diagnoses and reductions in adverse outcomes.